Flood Disaster Adaptation In Mentawai District Based On Local Wisdom: Comparative Study Of Disaster-Friendly Houses (Uma) - Rahmadani Siregar, Dewi; barlian, eri; syah, nurhasyan; razak, abdul; diliarosta, skunda (Sam Ratulangi University, 2024)
In the last decade, the intensity and quality of disaster threats in the Islands Mentawai have been the tallest. Experience has given birth to local wisdom in adapting to natural disasters, especially flood problems. One of the local pearls of wisdom possessed by the Mentawai people to adapt to floods is disaster-friendly houses ( Uma ). So this article was constructed to examine Uma's axiology in dealing with floods. The research method used is a qualitative approach, where data collection techniques use interviews and observation. In-depth interviews were conducted with two different community groups, namely the elite group and the lay community group consisting of 3 elite groups; traditional leaders, religious leaders, community leaders, and 20 general public groups. Data validation was carried out using triangulation techniques and analyzed through data reduction, data presentation, and concluding/verification. Research findings show that Uma has strong adaptive and mitigating powers in dealing with flood disasters. Uma can be compared to the construction of developed countries such as Japan, the Netherlands, and England in adapting to flood risks. Increasingly complex climatic conditions, together with the consequences of inappropriate tourism expansion and weak land use management, have led to an increase in the frequency and severity of flooding in the Mentawais – saltwater intrusion, temperature changes, weather changes, and landslides. The Mentawai region is increasingly vulnerable to the risk of saltwater intrusion, which affects the ability to supply clean water and develop regional infrastructure. Rainfall combined with higher tides has caused an increase in the extent of flooding, especially in the lowland areas of Mentawai Regency Keywords : Flood Disaster Adaptation ; Uma ; Local wisdom ; Mentawai